Risk assessment of non-native fishes in the Balkans Region using FISK, the invasiveness screening tool for non-native freshwater fishes - SIMONOVIC, P.; TOŠIĆ, A.; VASSILEV, M.; APOSTOLOU, A.; MRDAK, D.; RISTOVSKA, M.; KOSTOV, V.; NIKOLIĆ, V.; ŠKRABA, D.; VILIZZI, L.; COPP, G.H. (Mediterranean Marine Science, 2013)
A high level of freshwater fish endemism in the Balkans Region emphasizes the need for non-native species risk assessments to inform management and control measures, with pre-screening tools, such as the Fish Invasiveness Screening Kit (FISK) providing a useful first step. Applied to 43 non-native and translocated freshwater fishes in four Balkan countries, FISK reliably discriminated between invasive and non-invasive species, with a calibration threshold value of 9.5 distinguishing between species of medium and high risk sensu lato of becoming invasive. Twelve of the 43 species were assessed by scientists from two or more Balkan countries, and the remaining 31 species by a single assessor. Using the 9.5 threshold, three species were classed as low risk, 10 as medium risk, and 30 as high risk, with the latter category comprised of 26 moderately high risk, three high risk, and one very high risk species. Confidence levels in the assessments were relatively constant for all species, indicating concordance amongst assessors.